Rancang Bangun Game Edukasi Pada Pokok Bahasan Kinematika Berbasis MATLAB - Nurullaeli Nurullaeli; Alpi Mahisha Nugraha (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The aim of our research is to create an educational game on the subject of kinematics based on MATLAB program. Educational games are made using the MATLAB programming algorithm packaged in the form of Graphical User Interface (GUI). Our educational games can be used as one of the innovations of learning media to increase student interesting in physics and at the same time to provide other examples of the application of the MATLAB GUI in addition to being a calculation, analysis, and simulation tool in physics. This educational game based on MATLAB presents kinematics questions in a more attractive and enjoyable. With this educational game, students able to learn both of kinematics and MATLAB programming at the same time.